Technological bases of projecting distance learning courses - A. O. Kucheriavyi (Academy of Cognitive and Natural Sciences, 2017)
The purpose of the research: determining the technological basis for projecting distance learning courses. Objectives of the research: structuring technology projecting distance learning courses in stages; determination of the nature and characteristics of each of the projecting stages. Research methods: theoretical analysis, synthesis, generalization and modeling. The results of the research. The separate components of technology projecting of distance courses there are four stages. On the stage of creation the programs of distance learning course are determined its general aims, themes, which studies of separate themes, and its maintenance. The structuring stage of the course by modules envisages determinations separate components by contents that require successive working. Psychological peculiarities of the process of learning are taken into account at the stage of defining educational tasks for each module. The stage of development of requirements to the methodical providing of the on-line training course's modules is predefined by the necessity of taking into account of features of study of educational material exactly in the process of distance studies. The main conclusions and recommendations. Development of the distance course requires its prior projecting on technological principles. The observance of corresponding technology will allow to produce intention of course and create it didactics model as required element of course development.